Estudo acústico da fala traqueoesofágica - Reis, Nathália dos (2018)
This research integrates the field of the investigations of the alaryngeal speech with support of the field of Acoustic Phonetics. The aim of this study was to analyze, from an acoustic point of view, the quality of the tracheoesophageal speech and the characteristics of the stops consonants and the adjacent vowels produced by the APE. From an initial group of 22 subjects (17 total laryngectomized and 05 not submitted to treatments for laryngeal cancer), 15 comprised the groups studied as follows: ALA group (10 albedo speakers with PTE, distributed in groups: ALAa: five speakers, age ± 64 years and ALAb: five speakers, age ± 57 years) and LAR group (five laryngeal speakers, age ± 47 years). The data collection procedure (audio recordings) was performed at the Laryngectomized Outpatient Clinic of the Head and Neck Surgery Sector of the Medical School of Ribeirão Preto and at the Integrated Laboratory of Acoustic Analysis and Cognition of PUC-SP. The corpus of the research consisted of six words with the structure CVCV (Consonant - Vowel - Stop Consonant - Vowel), disyllables and paroxitones inserted in a vehicle sentence. In order to meet the objectives, two instruments of analysis were elaborated: a System of Acoustic Classification of the Quality of the Tracheoesophageal Speech and a script, applicable to the PRAAT software, for extracting acoustic measures of stop consonants, highlighting the information regarding voicing contrast (set of 44 measures related to duration, fundamental and formants frequency, and the intensity of adjacent consonants and vowels). The results were analyzed by means of descriptive statistics and multivariate analysis (Discriminant Analysis and Principal Component Analysis). The Quality Acoustic Classification System of Tracheoesophageal Speech revealed three relevant dimensions, in descending order of influence: measures characteristic of the sonority source (harmonics); the vocal tract resonances (formants) and the source of transient noise of stop consonants and adjacent vowels. These dimensions were the subdivision of the ALA speakers group (ALAa: acoustic quality of upper tracheoesophageal speech and ALAb: mean and lower limits). Speech samples from the ALAa and ALAb subgroups revealed a limitation of the maximum harmonic frequency, in relation to the LAR group, in addition to an increase in durations and voicing percentage in non-voiced segments, in a higher proportion in the ALAb subgroup. The influential variables referred to harmonic measurements and those related to the occlusion phase. For discriminant analysis of voicing contrast, considering pairs per point of articulation, the percentages of classification were 89.29% in bilabial sounds, 93.06% in alveolar sounds and 86.75% in velar sounds. The acoustic findings revealed a wide range of mobilizations developed by the alarygeal speakers in the pursuit of the goal of articulated and intelligible speech production